USING VIDEO BLOGGING AS AN APPROPRIATE MEDIA FOR TEACHING ENGLISH: BRING A LIVE CLASSROOM - Erik Pratama; Karisti . (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2018)
This study was aimed at investigating the use of Video Blogging (Vlog) as an appropriate media for teaching English. The study used qualitative case study as a tool to collect and analyze the data. Thirteen general high school students were chosen as the participants of this study. The data was collected through CAC questionnaire model as proposed by Schiffma & Kanuk (2004). The data from questionnaire demonstrated that the students showed positive response toward the use of Vlog in teaching English, since the overall mean of the students’ response (3.90) is higher than the neutral score (3.00). Most students felt that the use of Vlog lead to produce a good performance in an English class.